The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1210/jc.2005-0299
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lys173Arg Polymorphism withCYP11B2Expression in Normal Adrenal Glands and Aldosterone-Producing Adenomas

Abstract: A CYP11B2 haplotype including -344T and K173 is associated with higher gene expression than the -344C/R173 haplotype, supporting reported associations of -344T with higher aldosterone production and blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Higher aldosterone synthase gene expression and elevation of blood pressure were reported in a case of mice fed with high salt diet (Makhanova et al, 2008). In another report, CYP11B2 gene polymorphism was associated with higher gene expression in -344C/R173 haplotype (Tanahashi et al, 2005). The association of RAAS genes encoding renin (Mohana Vamsi et al, 2013), angiotensinogen (Srivastava et al, 2012a), angiotensinconverting enzyme (Srivastava et al, 2012b;Chandra et al, 2014a), angiotensin II type 1 receptor (Chandra et al, 2014b), and aldosterone synthase (CYP11B2) (Rajan et al, 2010) with essential hypertension has been recently studied in the Indian population.…”
Section: Introductionmentioning
confidence: 90%
“…Higher aldosterone synthase gene expression and elevation of blood pressure were reported in a case of mice fed with high salt diet (Makhanova et al, 2008). In another report, CYP11B2 gene polymorphism was associated with higher gene expression in -344C/R173 haplotype (Tanahashi et al, 2005). The association of RAAS genes encoding renin (Mohana Vamsi et al, 2013), angiotensinogen (Srivastava et al, 2012a), angiotensinconverting enzyme (Srivastava et al, 2012b;Chandra et al, 2014a), angiotensin II type 1 receptor (Chandra et al, 2014b), and aldosterone synthase (CYP11B2) (Rajan et al, 2010) with essential hypertension has been recently studied in the Indian population.…”
Section: Introductionmentioning
confidence: 90%
“…After an extensive selection according to the inclusion criteria (Fig. 1), seven studies [14][15][16][17][18][19][20] (621 cases and 1027 controls) on T-344C polymorphism, three studies [18,20,21] (327 cases and 336 controls) on A2718G polymorphism were included for meta-analyses. Detailed characteristics of the eight eligible studies and the genotype distributions of the two tested polymorphisms were listed in Table 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…This is based on the evidence suggesting functional relevance or reports of association with hypertension. [11][12][13]17 Two SNPs span the CYP11B2 gene: rs1799998 in the promoter region (also known in previous publications as C-344T or SF-1) and rs4539 in the third exon (also known as A2718G or K173R). Two SNPs span the CYP11B1 gene: rs 6410 (G225A) in the first exon and rs6387 (A2803G) in the third intron.…”
Section: Genotypingmentioning
confidence: 99%
“…9,10 Inglis et al 11 found that the frequencies of the rs1799998T allele and the intron 2 conversion allele in the CYP11B2 gene were markedly higher in Conn's syndrome group than in the normal control group, which demonstrated that the relative genotypes may predispose the tumor to aldosterone production. Tanahashi et al 12 considered that a CYP11B2 haplotype, including À344T and K173 in APA, was associated with a higher gene expression than the À344C/R173 haplotype.…”
Section: Introductionmentioning
confidence: 99%